Pemanfaatan Media Belajar Oleh Guru Dalam Pembelajaran Di SD Negeri 1 Mata Ie Kabupaten Aceh Besar - Zharifah Munawarah Munawarah; Bukhari Bukhari; Aida Fitri (Jurnal Ilmiah Mahasiswa Pendidikan Guru Sekolah Dasar, 2022)
This study aims to describe the use of learning media in SD Negeri Mata ie Aceh Besar. The research method used is descriptive qualitative. The research instrument used interviews and observation. Based on the results of the study, it was found that teachers used visual media, print media, image media, LCD, and video media. All of these media are used according to the characteristics of the media. Thus, it can be concluded that teachers use learning media according to their needs. It is expected that the school will support the procurement of teaching media according to the needs of students, and for teachers to be able to utilize learning media in learning so that learning activities can be carried out correctly.Key Words : Utilization of Learning Media, Learning